Investing in Logistics for Sustainable Economic Growth : Background Studies for the Preparation of Cambodia Logistics Master Plan - World Bank Group (World Bank, Phnom Penh, 2018)
The World Bank prepared three background studies as inputs for the development of the Cambodia Logistics Master Plan led by the Royal Government of Cambodia (RGC) in 2017–2018. These studies benefit from a close coordination and collaboration with Japan International Cooperation Agency (JICA) that focused its assessment on transport infrastructure and connectivity. The key findings and recommendations are summarized into four parts in respect of the three background studies: (a) an update of trade competitiveness, (b) a review of the legal and regulatory framework of the logistics sector in Cambodia, and (c) a design of the monitoring and evaluation (M&E) framework for the proposed Cambodia Logistics Master Plan.